The Feminist Potential of Beatrice Helen Barmby’s Gísli Súrsson: A Drama - Katarskytė, Auksė Beatričė (Scandinavistica Vilnensis, 2023)
The late Victorian Britain was fascinated with the ancient North. British literary authors of the second half of the nineteenth century sought inspiration for their novels, poems, and plays in medieval Icelandic imagery. One of these authors was Beatrice Helen Barmby, author of Gísli Súrsson: A Drama. Since her authorship has largely been forgotten, this paper is an attempt to reintroduce her as one of the Victorian enthusiasts of Old Norse literature. Gísli Súrsson: A Drama (1900) is a play based on the medieval Gísla saga Súrssonar. Notably, the adaptation centres around the relationships between the main characters rather than the existential drama of the outlaw Gísli. I argue that the play can be interpreted as an invitation to consider women’s rights, or the Woman Question, a topic which excited heated debates in late nineteenth-century Britain. The play’s depiction of marriage is especially close to the early liberal feminist critique of the inferior role of women as harmful for both women and men. On the other hand, the play portrays Gísli’s wife Aud as a universally stoic and moral character, a domestically emancipated free woman. This paper thus analyses Gísli Súrsson: A Drama as a Victorian work on Old Norse-inspired themes with activist potential.
Keywords: medievalism; saga adaptation; Victorian reception of Old Norse literature; First Wave feminism